Characterization of an IncR Plasmid with Two Copies of ISCR-Linked qnrB6 from ST968 Klebsiella pneumoniae. (24th November 2020) - Qian, Changrui; Zhu, Xinyi; Lu, Junwan; Shen, Kai; Chen, Qianqian; Zhou, Wangxiao; Liu, Hongmao; Lu, Wei; Zhou, Danying; Sun, Zhewei; Lin, Xi; Li, Kewei; et al.
Abstract : To characterize the molecular structure of IncR plasmid-related sequences, comparative genomic analysis was conducted using 261 IncR plasmid backbone-related sequences. Among the sequences, 257 were IncR plasmids including the multidrug-resistance IncR plasmid pR50-74 from Klebsiella pneumoniae strain R50 of this work, and the other four were from bacterial chromosomes. The IncR plasmids were derived from different bacterial genera or species, mainly Klebsiella pneumoniae (70.82%, 182/257), Escherichia coli (11.28%, 29/257), Enterobacter cloacae (7.00%, 18/257), and Citrobacter freundii (3.50%, 9/257). The bacterial chromosomes carrying IncR plasmid backbone sequences were derived from Proteus mirabilis AOUC-001 and Klebsiella pneumoniae KPN1344, among others. The IncR backbone sequence of P. mirabilis AOUC-001 chromosome shows the highest identity with that of pR50-74. Complex class 1 integrons carrying various copies of IS CR1-sdr-qnrB6-△qacE/sul1 (IS CR1 -linked qnrB6 unit) were identified in IncR plasmids. In addition to two consecutive copies of qnrB6 - qacE - sul1, the other resistance genes encoded on pR50-74 are all related to mobile genetic elements, such as IS 1006, IS 26, and the class 1 integron. This study provides a clear understanding of the mobility and plasticity of the IncR plasmid backbone sequence and emphasizes the important role of IS CR in the recruitment of multicopy resistance genes.